2017
DOI: 10.1186/s13059-017-1362-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling of human gliomas reveals macrophage ontogeny as a basis for regional differences in macrophage activation in the tumor microenvironment

Abstract: BackgroundTumor-associated macrophages (TAMs) are abundant in gliomas and immunosuppressive TAMs are a barrier to emerging immunotherapies. It is unknown to what extent macrophages derived from peripheral blood adopt the phenotype of brain-resident microglia in pre-treatment gliomas. The relative proportions of blood-derived macrophages and microglia have been poorly quantified in clinical samples due to a paucity of markers that distinguish these cell types in malignant tissue.ResultsWe perform single-cell RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
498
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(583 citation statements)
references
References 52 publications
51
498
2
1
Order By: Relevance
“…All three of the TAM populations, particularly clusters 23 and 28, were among the monocytic clusters with the highest expression of the canonical M2 signature, but were likewise high in the M1 signature (Figure S7E). Quite strikingly, we found that M1 and M2 gene signatures positively correlated in the myeloid populations (Figure 7G), in line with recent findings in other tumor types (Muller et al, 2017). These findings support the idea that macrophage activation in the tumor microenvironment does not comport with the polarization model, either as discrete states or along a spectrum of alternative polarization trajectories.…”
Section: Resultssupporting
confidence: 91%
“…All three of the TAM populations, particularly clusters 23 and 28, were among the monocytic clusters with the highest expression of the canonical M2 signature, but were likewise high in the M1 signature (Figure S7E). Quite strikingly, we found that M1 and M2 gene signatures positively correlated in the myeloid populations (Figure 7G), in line with recent findings in other tumor types (Muller et al, 2017). These findings support the idea that macrophage activation in the tumor microenvironment does not comport with the polarization model, either as discrete states or along a spectrum of alternative polarization trajectories.…”
Section: Resultssupporting
confidence: 91%
“…Muller et al . demonstrate that infiltrating macrophages rather than resident microglia encode immunosuppressive cytokines within the GBM microenvironment . Thus, immunosuppressive pathways operating in the GBM‐free brain are utilized and extended upon by infiltrating myeloid cells, contributing to the extensive immunosuppressive network.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of genes such as HAVCR2 and its ligand LGALS9 and CD274, together with TGFB2 and IL-10, safeguard the normal brain against excessive inflammation [48]. Muller et al demonstrate that infiltrating macrophages rather than resident microglia encode immunosuppressive cytokines within the GBM microenvironment [49]. Thus, immunosuppressive pathways operating in the GBM-free brain are utilized and extended upon by infiltrating myeloid cells, contributing to the extensive immunosuppressive network.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of genes such as HAVCR2, its ligand LGALS9 and CD274, along with TGFB2 and IL10 safeguard the normal brain against excessive inflammation (43). Muller et al demonstrate that infiltrating macrophages rather than resident microglia encode immunosuppressive cytokines within the GBM microenvironment (44). Thus, immunosuppressive pathways operating in the GBM-free brain are utilised and extended upon by infiltrating myeloid cells, contributing to the extensive immunosuppressive network.…”
Section: Multiple Mechanisms Of Tumour-mediated Downregulation Of Nk mentioning
confidence: 99%